K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

a,x3=1

x=1

b,(x-5)2=16

(x-5)2=42

x-5=4

x=9

c,3x=92

3x=34

x=4

d,2x.27:25=1024

2x+7-5=210

x+7-5=10

x=8

17 tháng 9 2017

a) x3 = 1

    x3 = 13

    x   = 1

b) (x - 5)= 16

    (x - 5)2 = 42

     x - 5    = 4 

     x         = 4 + 5 

      x        =    9

c) 3x = (32)2

   3x   = 34

    x   = 4

d) 2x . 27 : 25 = 1024

    2. 2: 25 = 210

     2x + 7 - 5     = 210

       x + 7 - 5 = 10

       x            = 10 + 5 - 7

       x            = 8

Chúc bạn học giỏi nha.

18 tháng 10 2017

\(a,\left(27x+6\right):3-11=9\)

\(\Rightarrow\left(27x-6\right):3=20\)\(\Rightarrow27x-6=60\)\(\Rightarrow27x=66\)\(\Rightarrow x=\frac{22}{9}\)

\(b,\left(15-6x\right).3^5=3^6\)

\(\Rightarrow15-6x=3\)\(\Rightarrow6x=12\)\(\Rightarrow x=2\)

\(c,\left(2x-6\right).4^7=4^9\)

\(\Rightarrow2x-6=16\)\(\Rightarrow2x=22\)\(\Rightarrow x=11\)

18 tháng 10 2017

Bài 1: Tìm x

a,(27.x+6):3-11=9

﴾ 27x + 6﴿ : 3 ‐ 11 = 9

﴾ 27x + 6﴿ : 3 = 20

27x + 6 = 60

27x = 54

    x = 54 : 27

    x = 2 

Vậy x = 2

b,( 15-6x ) . 35=36

( 15 - 6x ) = 36 : 35

15 - 6x = 3

       6x = 15 - 3

       6x = 12

         x = 12 : 6

         x = 2

Vậy x = 2

c,( 2x-6 ) . 47=49

2x - 6 = 49 : 47

2x - 6 = 16

2x      = 16 + 6

2x      = 22

  x      = 22 : 2

  x      = 11

Vậy x = 11

15 tháng 7 2019

\(\left[x^2\right]^4\cdot16=2^{20}\)

\(\Leftrightarrow x^8\cdot16=2^{20}\)

\(\Leftrightarrow x^8\cdot2^4=2^{20}\)

\(\Leftrightarrow x^8=2^{20}:2^4\)

\(\Leftrightarrow x^8=2^{16}\)

\(\Leftrightarrow x^8=\left[2^2\right]^8\)

\(\Leftrightarrow x^8=4^8\Leftrightarrow x=4\)

\(2^{x+3}+2^x=144\)

\(\Leftrightarrow2^x\cdot2^3+2^x=144\)

\(\Leftrightarrow2^x\left[2^3+1\right]=144\)

\(\Leftrightarrow2^x\cdot9=144\)

\(\Leftrightarrow2^x=16\Leftrightarrow x=4\)

Bài cuối tt

15 tháng 7 2019

X^8=2^16  =>X=4

2^X(2^3+1)=144

=>2^X=16

=>X=4

3^3X(2^2-1)=9^5

=>3^3X=3^9

=>X=3

25 tháng 8 2016

6

8

2

4

5

2

3

7x-x=521:519+3.22-70

=> 6x = 5^2 + 12 -1

=> 6x = 36

=> x = 36/6 = 6

Kết quả 6

Học tốt

24 tháng 6 2016

 a,  4x + 13 =29

      4x = 29 - 13

      4x = 16

      4x = 42

=> x = 2